Francisella novicida-Containing Vacuole within Dictyostelium discoideum: Isolation and Proteomic Characterization - Marecic, Valentina; Shevchuk, Olga; Link, Marek; Viduka, Ina; Ozanic, Mateja; Kostanjsek, Rok; Mihelcic, Mirna; Antonic, Masa; Jänsch, Lothar; Stulik, Jiri; Santic, Marina (Microorganisms, 2024)
Francisella is a highly infectious gram-negative bacterium that causes tularemia in humans and animals. It can survive and multiply in a variety of cells, including macrophages, dendritic cells, amoebae, and arthropod-derived cells. However, the intracellular life cycle of a bacterium varies depending on the cell type. Shortly after the infection of mammalian cells, the bacterium escapes the phagosome into the cytosol, where it replicates. In contrast, in the amoebae Acanthamoeba castellanii and Hartmannella vermiformis, the bacterium replicates within the membrane-bound vacuole. In recent years, the amoeba Dictyostelium discoideum has emerged as a powerful model to study the intracellular cycle and virulence of many pathogenic bacteria. In this study, we used D. discoideum as a model for the infection and isolation of Francisella novicida-containing vacuoles (FCVs) formed after bacteria invade the amoeba. Our results showed that F. novicida localized in a vacuole after invading D. discoideum. Here, we developed a method to isolate FCV and determined its composition by proteomic analyses. Proteomic analyses revealed 689 proteins, including 13 small GTPases of the Rab family. This is the first evidence of F. novicida-containing vacuoles within amoeba, and this approach will contribute to our understanding of host-pathogen interactions and the process of pathogen vacuole formation, as vacuoles containing bacteria represent direct contact between pathogens and their hosts. Furthermore, this method can be translocated on other amoeba models.
Keywords: vacuole; Dictyostelium; proteome; amoeba; intracellular life; Francisella